Trials on Induced Ovulation of Fugu niphobles (Jordan and Snyder) with Human Chorionic Gonadotropin - Cheah, S. H.; Satoh, H. (1989)
The effect of administration of HCG (Human Chorionic Gonadotropin) on ovulation of Fugu niphobles was studied. The female fish which exhibited distended abdomen were randomly assigned to four groups and the treatments for groups 1, 2, 3 and 4 were 0, 100, 200 and 300 I. U of HCG per fish respectively. The fish were injected immediately after the groups were established and unovulated females were reinjected after 72 hours. The dosage for each fish was calculated based on the body weight and expressed as 1.U/g body weight. The ovulatory success in fish administered with 0, 1, 2, 3 and 41. U of HCG/g body weight was 40%, 83 %, 70%, 90% and 80% respectively. This indicated that fish in the control group could also ovulate in captivity and that administration of HCG would enable a higher degree of ovulatory success.